Quantity of within-sport distance variety - what can pool swimmers and track runners learn from each other? - Born, D.-P.; Lorentzen, J.; Björklund, G.; Ruiz-Navarro, J. J. (Frontiers in Sports and Active Living, 2024)
Objective: To determine the relationship between success at peak performance age and quantity of within-sport distance variety and compare the dose-time-effect between swimming and track running by determining probability of becoming an international-class female athlete based on the number of different race distances the athletes compete in each year throughout their development process.